(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
Vildagliptin is a dipeptidylpeptidase-4 (DPP-4) inhibitor class of anti-diabetic drug, which gets rapidly absorbed following oral administration and then required to administer twice a day. An attempt has been made to extend the release up to 24 h using various hydrophilic and hydrophobic polymers such as xanthan gum, guar gum (GG); hydroxypropyl methylcellulose and ethyl cellulose at different ratios were used. The wet granulation technique was employed for the preparation of tablets. The prepared tablets were characterized for pre- and postcompression parameters. The Fourier transform infrared study indicated no interaction between the drug and polymers. Formulation F10 having 30% GG and 10% ethyl cellulose showed better results. The drug release kinetic data confirmed that the optimized tablets best fit in to Higuchi model, which had shown a R2 value of 0.988. The results of the in vitro release data were fitted to the Korsemeyerâ€“Peppaâ€™s equation to analyze the release pattern of the drug from the polymeric system. The value of â€œnâ€ was found to be more than 0.89, indicating the drug release follows super case II transport. Optimized tablets showed no significant changes in the physical appearance, drug content, in vitro dissolution pattern after storage at 40Â°C/75% relative humidity for 3 months. It indicates good stability of vildagliptin extended release tablets.